An epicardial floor plan for building and rebuilding the mammalian heart. - Riley, P (2012)
The epicardium is a mesothelial cell layer which contributes to the coronary vessels and myocardium and acts as an important source of trophic signals to maintain continued growth and differentiation of the developing heart. The precise lineage potential of the embryonic epicardium has come under recent scrutiny with notable questions around its capacity to give rise to derivative vascular endothelial cells and cardiomyocytes. The importance of the epicardium is not restricted to heart formation. Recent studies in the adult heart have highlighted a paracrine role in modulating injury and have begun to realize its potential as a source of progenitor cells (EPDCs) which may be reactivated toward facilitating neovascularization and myocardial repair after ischemic injury. Thus, the adult epicardium has an embryological origin and emerges as a prime exemplar of the paradigm of activated resident stem cell therapy in regenerative medicine, whereupon a major goal is to restore embryonic plasticity to otherwise dormant adult progenitors and facilitate organ repair. In this review, we will explore current thinking on the origins of the epicardium, its role as a signaling center, lineage heterogeneity, and controversy around epicardial potential within the developing heart. We will extrapolate to the adult injury setting, drawing on key studies in zebrafish and mouse which establish the basis for the adult epicardium as a target for cardiovascular regeneration. Finally, we will consider translation of this potential to the human lineage alongside the prospects for discovery of target cell-based therapeutics.